Accumulative Pension as a Tool for the Development of the Pension System of the Russian Federation ("Journal "U". Economy. Management. Finance.", 2020)
The article discusses the features of the distribution and mixed pension systems, the level of pension savings in 2019 in various countries of the world community, analyzes the investment potential of the funded element of the pension system.
Keywords: pension system; pension; funded part; economy; investments